Pengaruh Kombinasi Agregat Halus dan Volume Foam terhadap Sifat Mekanik Beton Busa - Naifah, Naifah; Sabila, Ghaitsa Zahira; Bahri, Syamsul; Miswar, Khairul (Politeknik Negeri Lhokseumawe, 2025)
Lightweight concrete is defined as concrete utilizing lightweight aggregates or a combination of fine aggregates and natural sand, with a maximum density not exceeding 1850 kg/m³. Recent advancements in foam concrete—a cement-based material with a density range of 400–1850 kg/m³—have expanded its applications in structural and non-structural components. This study investigates the effect of fine aggregate particle size and foam volume on the compressive strength of lightweight foam concrete. Fine aggregates with particle sizes of 4.75 mm, 2.36 mm, and 1.18 mm were used, corresponding to target densities of 800 kg/m³, 1000 kg/m³, and 1200 kg/m³. The mix design was based on the Absolute Volume Method, following ASTM C29 and SNI standards. Experimental results indicate that the use of 4.75 mm aggregate resulted in the highest percentage increase in compressive strength across all dencity levels, namely 1.50% at 800 kg/m³, 2.08% at 1000 kg/m³, and 1.34% at 1200 kg/m³. At the highest density (1200 kg/m³), where foam content was minimized, the increase in compressive strength was more stable, recorded at 1.06% for 1.18 mm sand, 1.28% for 2.36 mm sand, and 1.34% for 4.75 mm sand. The findings highlight that both aggregate gradation and foam volume significantly affect the mechanical performance of foam concrete, with coarser aggregates offering better strength performance, particularly at higher densities.